Role of vitamin C and SVCT2 in neurogenesis - Salazar, Katterine; Jara, Nery; Ramírez, Eder; de Lima, Isabelle; Smith-Ghigliotto, Javiera; Muñoz, Valentina; Ferrada, Luciano; Nualart, Francisco (Frontiers in Neuroscience, 2023)
Different studies have established the fundamental role of vitamin C in proliferation, differentiation, and neurogenesis in embryonic and adult brains, as well as in in vitro cell models. To fulfill these functions, the cells of the nervous system regulate the expression and sorting of sodium-dependent vitamin C transporter 2 (SVCT2), as well as the recycling of vitamin C between ascorbic acid (AA) and dehydroascorbic acid (DHA) via a bystander effect. SVCT2 is a transporter preferentially expressed in neurons and in neural precursor cells. In developmental stages, it is concentrated in the apical region of the radial glia, and in adult life, it is expressed preferentially in motor neurons of the cerebral cortex, starting on postnatal day 1. In neurogenic niches, SVCT2 is preferentially expressed in precursors with intermediate proliferation, where a scorbutic condition reduces neuronal differentiation. Vitamin C is a potent epigenetic regulator in stem cells; thus, it can induce the demethylation of DNA and histone H3K27m3 in the promoter region of genes involved in neurogenesis and differentiation, an effect mediated by Tet1 and Jmjd3 demethylases, respectively. In parallel, it has been shown that vitamin C induces the expression of stem cell-specific microRNA, including the Dlk1–Dio3 imprinting region and miR-143, which promotes stem cell self-renewal and suppresses de novo expression of the methyltransferase gene Dnmt3a. The epigenetic action of vitamin C has also been evaluated during gene reprogramming of human fibroblasts to induced pluripotent cells, where it has been shown that vitamin C substantially improves the efficiency and quality of reprogrammed cells. Thus, for a proper effect of vitamin C on neurogenesis and differentiation, its function as an enzymatic cofactor, modulator of gene expression and antioxidant is essential, as is proper recycling from DHA to AA by various supporting cells in the CNS.